Hubungan antara kecerdasan emosi dan komitmen pekerja : kajian di kalangan pegawai polis - Rogis, Bin Baker (Universiti Malaysia Sarawak, (UNIMAS), 2010)
This study was conducted to determine the relationship between Emotional Intelligence (Intrapersonal and Interpersonal) and the level of job commitment among Police Officer in Kuching, Sarawak. The instrument used was a set of standard questionnaires that was distributed to 300 respondents where a total of 288 respondents had sent back the questionnaires. This study was carried out quantitatively and the findings of this study were analyzed using descriptive and inferential analysis with the aid of Statistical Packages for Social Science (SPSS version 18.0 for windows). The results of this study found that the levels of Intrapersonal Emotional Intelligence, Interpersonal Emotional Intelligence level and the level of job commitment among police officers are very high. A significant relationship existed between Intrapersonal Emotional Intelligence and level of commitment to work among police officers. The findings also showed a strong significant relationship between the level of Interpersonal Emotional Intelligence and the level of commitment to their work. The results of this study would be a point of reference and able to assist in the aspect of human resource development especially with regards to the Emotional Intelligence and work commitments in the organization of the Royal Malaysia Police (PDRM).